Effect of eTansiyon smartphone application on hypertension control - YILMAZ, EMRE; UZUNER, ARZU; DOĞAN, BUKET; ALTIKARDEŞ, ZEHRA AYSUN; AKDENİZ, ESRA (My University, 2022)
Aim: To investigate the effectiveness of eTansiyon smartphone application in blood pressure control in patients with hypertension. Background: Global prevalence of hypertension and the burden of chronic illness care, especially in primary care, are increasing in world. We have developed eTansiyon to ensure the continuity of patient-physician relationship, so it may help to improve the lifestyle of patients with hypertension, increase their adherence to treatment and achieve the target blood pressure. Methods: This study was a non-randomized controlled study. The sample was selected by random sampling method among the patients registered in 6 Family Health Units (FHUs). Randomization was performed at the FHU level; the units were randomized to 4 control group (CG) and 2 intervention group (IG), so that randomization in this study was 2:1. Both groups were followed up for at least four months. In addition to CG, IG were provided to use eTansiyon. Obtained data were analysed to evaluate differences between groups at the beginning and end of the study, intra-group changes after follow-up and interaction between groups and follow-up period. Findings: The study was performed with 124 patients in CG and 61 patients in IG. At the end of the study, the average systolic blood pressure/diastolic blood pressure (SBP/DBP) of office and home was significantly lower in IG compared to CG (P < 0.001, MD 9.5 mmHg; P = 0.007, MD 3.8 mmHg; P < 0.001, MD 10.6 mmHg; P < 0.001, MD 4.8 mmHg, respectively), and it was found that the proportion of people with target blood pressure in IG was significantly higher than CG (P < 0.001, 49.2%(n = 30) and 22.6%(n = 28), respectively). Repeated measures ANOVA and generalized estimating equations results showed that follow-up period and interaction between groups were significant in terms of office and home SBP/DBP and target blood pressure level during follow-up period (P < 0.001, P < 0.001, P < 0.001, P < 0.001, P < 0.024, respectively).
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; BİRİNCİL SAĞLIK BAKIMI; Klinik Tıp; Klinik Tıp (MED); PRIMARY HEALTH CARE; CLINICAL MEDICINE; Clinical Medicine (MED); blood pressure; hypertension management; mobile application; patient-centred care; primary care; smartphone; INTERVENTION; PREVALENCE; MANAGEMENT; AMERICAN; VALIDITY; DISEASE; blood pressure; hypertension management; mobile application; patient-centred care; primary care; smartphone